Size and depth of cold-water coral colonies on 3D reconstructions in the Lacaze-Duthiers canyon, CALADU_2019 ... - Fabri, Marie-Claire (SEANOE, 2019)
Coral assemblages were reconstructed in 3 dimensions (photogrammetry) using the 'Structure from motion' technique, at several locations in the canyon. The two colonial species, M. oculata and D. pertusum, were located on georeferenced photogrammetric models, with geographic coordinates and depths. The size distribution of both species was measured on photogrammetric models. Population size structure Number of coral colonies measured = 5387 (COVID containment period) of which - 851 D. pertusum colonies - 4536 colonies of M. oculata Average size : - D. pertusum = 28 cm high (standard deviation = 15 cm) - M. oculata = 18 cm (standard deviation = 7 cm) Maximum sizes recorded on dives 143-05 and 145-07 at around 330 m depth: - D. pertusum = 88 cm - M. oculata =50 cm Length of large colony bushes : - D. pertusum = up to 2.5 m - M. oculata = up to 1.8 m Both species showed differences in average size depending on the sites explored (Fig. 6). For D. pertusum, dives 143-05 and 145-07 revealed larger populations with ...